Pathogenicity of Vibrio parahaemolyticus causing acute hepatopancreatic necrosis disease (AHPND) in shrimp (Litopanaeus vannamei) in Serang, Banten, Indonesia - AFANDI SAPUTRA; MAFTUCH MAFTUCH; SRI ANDAYANI; UUN YANUHAR (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Saputra A, Maftuch, Andayani S, Yanuhar U. 2023. Pathogenicity of Vibrio parahaemolyticus causing acute hepatopancreatic necrosis disease (AHPND) in shrimp (Litopanaeus vannamei) in Serang, Banten, Indonesia. Biodiversitas 24: 2365-2373. Vannamei shrimp target EMS (Early Mortality Syndrome)/AHPND (Acute Hepotopancreatic Necrosis Disease) cases in several Asian nations, including China, Vietnam, Malaysia, Thailand, India, and Indonesia. AHPND cases on shrimp farms have been reported in several Indonesian regions. The aim of this study was to evaluate the histopathological pathogenicity of Vibrio parahaemolyticus in different shrimp tissues exposed to different doses and durations of exposure. PCR amplification of V. parahaemolyticus was performed using Vp.flaE-79F (5?-GCA GCT GAT CAA AAC GTT GAG T-3?) and Vp.flaE-934R (5?-GATACCTTGTTACGACTT -3?) primers for molecular identification of bacteria isolated from shrimp exhibiting AHPND symptoms. V. parahaemolyticus positive target band at 897 bp. Bacterial isolates with green colonies on TCBS agar media were chosen for other test. Challenge tests with healthy shrimp were conducted using the V. parahaemolyticus strain. The challenge test on shrimp demonstrated the same clinical and pathological symptoms as the signs of infected shrimp in rivers, including swimming into the container’s corner and changes in the carapace’s pale color and empty midgut. The results showed that challenged shrimp displayed necrosis, atrophy, granulomas, cell sloughing, and had significantly considerable hemocyte infiltration that led to melanization. The highest percentage (63.33%) of damage was recorded in the treatment with a concentration of 108 CFU mL-1. It was also observed that virulence of V. parahaemolyticus strain varied with different concentrations. At concentrations of 108 CFU mL-1 and 106 CFU mL-1, virulence of V. parahaemolyticus strain caused 100% mortality in 73 hour post-infection (p.i). The lowest concentration limit for pathogenicity was 104 CFU mL-1 with a mortality of 48% at 73 p.i. The challenge test results showed that V. parahaemolyticus strain that causes AHPND was the main pathogen affecting vannamei shrimp in Serang, Banten, Indonesia.